2008
DOI: 10.1063/1.2980505
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon resonances and electron phase shifts near Au nanospheres

Abstract: Articles you may be interested inSub-10 nm patterning of gold nanostructures on silicon-nitride membranes for plasmon mapping with electron energy-loss spectroscopy Surface plasmon resonance of gold nanoparticles formed by cathodic arc plasma ion implantation into polymer J.Determination of the aspect ratio statistical distribution of gold nanorods in solution from a theoretical fit of the observed inhomogeneously broadened longitudinal plasmon resonance absorption spectrum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This paper also reports the use of multiple image planes to obtain a better estimate of the longitudinal derivative. The same group [312] also used the transport of intensity equation to image the structure of MgO nano-cubes and also measure the mean inner potential of the cubes, and went on to use the transport of intensity equation to image phase shifts [313] that they attributed to surface plasmon excitation. This paper suggested that the phase retrieval techniques offer a new approach to the observation of such structures.…”
Section: Figure 20: Experimental Underfocused (A) and Overfocused Ele...mentioning
confidence: 99%
“…This paper also reports the use of multiple image planes to obtain a better estimate of the longitudinal derivative. The same group [312] also used the transport of intensity equation to image the structure of MgO nano-cubes and also measure the mean inner potential of the cubes, and went on to use the transport of intensity equation to image phase shifts [313] that they attributed to surface plasmon excitation. This paper suggested that the phase retrieval techniques offer a new approach to the observation of such structures.…”
Section: Figure 20: Experimental Underfocused (A) and Overfocused Ele...mentioning
confidence: 99%
“…Some novel ideas have been proposed on the detection side of SPP imaging. For instance, electron phase retrieval maps have been suggested in holographic electron microscopy, 94 and the direct electrical detection of SPPs [95][96][97] promises to be highly efficient, though not yet readily applicable to imaging. Even more advances have been made in recent years on the excitation side.…”
Section: Discussionmentioning
confidence: 99%
“…The TIE does not require any special microscope attachments or a vacuum region, and is thus considered to have a wider scope for applications compared to EH. The TIE has been used to determine the mean inner potential (MIP) of metallic nanoparticles [14][15][16], and it was found that the MIP increases as the particle diameter decreases to a few nanometers. Petersen et al…”
Section: / 24mentioning
confidence: 99%